Remote Ischaemic Conditioning after Stroke Trial (RECAST): a pilot randomised placebo controlled phase II trial in acute ischaemic stroke (ISRCTN 86672015) - England, Timothy J.; Hedstrom, Amanda; O'Sullivan, Saoirse; Donnelly, Richard; Barrett, David A.; Sarmad, Sarir; Sprigg, Nikola; Bath, Philip M.W. (American Heart Association, 2017)
Background: Repeated episodes of limb ischaemia and reperfusion (remote ischaemic conditioning, RIC) may improve outcome after acute stroke. Methods: We performed a pilot blinded placebo-controlled trial in patients with acute ischaemic stroke, randomised 1:1 to receive four cycles of RIC within 24 hours of ictus. The primary outcome was tolerability and feasibility. Secondary outcomes included safety, clinical efficacy (day 90), putative biomarkers (pre- and post intervention, day 4) and exploratory haemodynamic measures. Findings: Twenty-six patients (13 RIC, 13 sham) were recruited 15.8 hours (SD 6.2) post onset, age 76·2 years (10.5), blood pressure 159/83mmHg (25/11) and NIHSS 5 [IQR 3.75-9.25]. RIC was well tolerated with 49/52 cycles completed in full. Three patients experienced vascular events in the sham group: two ischaemic strokes and two myocardial infarcts versus none in the RIC group (p=0·076, log-rank test). Compared to sham, there was a significant decrease in day 90 NIHSS in the RIC group, median NIHSS 1 [0.5-5] versus 3 [2-9.5], p=0.04; RIC augmented plasma heat shock protein (HSP) 27 (p<0·05, repeated 2-way ANOVA) and phosphorylated HSP27 (p<0·001) but not plasma S100-beta, matrix metalloprotinase-9, endocannabinoids or arterial compliance. Conclusions: RIC after acute stroke is well tolerated and appears safe and feasible. RIC may improve neurological outcome and protective mechanisms may be mediated through HSP27. A larger trial is warranted. Clinical Trial Registration-URL: http://www.isrctn.com. Unique identifier: ISRCTN86672015